Aplicación de un sistema contable agropecuario, para la granja San Antonio, del cantón Marcabeli, provincia de El Oro, periodo junio – octubre del 2014 - Huanca Quezada, Edita Marlene (2015)
This research paper is entitled: Application of an accounting system AGRICULTURE FOR FARM SAN ANTONIO, CANTON MARCABELÍ, PROVINCE OF EL ORO, PERIOD JUNE - OCTOBER 2014, is aimed at solving the lack of an accounting cost control who has not allowed to know how much farm produce in San Antonio, three cost components: inputs and materials, labor and common operating costs, agricultural production costs pigs and the proper management of these three elements the cost for profit. The research objectives were accomplished by applying a cost accounting process for the poultry farm under study, first the initial inventory of the source documentation and physical verification of assets, rights and obligations established in the base, then the state baseline followed by the entire accounting process until the financial statements. Also the accounting control of the three elements of cost in both equipment and materials, labor and common operating costs to determine the unit and total pig production cost in a period extending from Juny to pig production was conducted October 2014, in order to fix the sales price. The main conclusion is the application of an accounting system of agricultural cost control process with its three elements mainly where common operating costs should be taken into account when determining the total and unit cost of each production well was recommended that the accounting process is used to generate the financial statements of agricultural costs